2022-RA-689-ESGO Fertility-sparing treatment in patients with IB1 cervical cancer – results of the international multicentre retrospective FERTISS study (ENGOT Cx14; CEEGOG Cx-03). (20th October 2022) - Slama, Jiri; Runnebaum, Ingo; Scambia, Giovanni; Angeles, Martina Aida; Bahrehmand, Kiarash; Kommoss, Stefan; Fagotti, Anna; Narducci, Fabrice; Matylevich, Olga; Holly, Jessica; Martinelli, Fabio; Koual, Meriem; et al.
Abstract : Introduction/Background: One of the key conditions for selecting candidates for fertility sparing treatment (FST) is a tumour size not exceeding 2 cm in the largest dimension. While there is a consensus on the choice of surgical treatment in stage IA, both radical (radical trachelectomy) and non-radical (simple trachelectomy or conisation) procedures are advocated in stage IB1, often depending on tumor size (>1 cm vs. 1–2 cm) and the presence of LVSI. Methodology: Patients with IB1 cervical cancer were recruited from the international multicenter retrospective FERTISS study. Inclusion criteria were lymph node negativity, age 18–40 years, and any type of FST, regardless of neoadjuvant chemotherapy, histotype, or tumour grade. Parameters representing disease and treatment characteristics were analyzed for risk of recurrence. Results: A total of 356 stage IB1 patients from 44 institutions in 13 countries were enrolled in the study. The mean age of the patients was 31.7 years, 70.2% of them were nulliparous. One-third of the tumours were adenocarcinomas and one-third of cases were LVSI positive. Oncological treatment characteristics are summarized in table 1 . During median follow-up of 72 months there were 27 recurrences (7.6%) and 8 deaths (2.3%) from the disease. Recurrence rates did not differ between patients after non-radical cervical procedures (conization or simple trachelectomy) and radical trachelectomy (7.5% vs. 7.7%; p=0.957), even after subgroup analysis according to tumour size (<1 cm: 5.2% vs. 7.4%; p=0.507; 1–2 cm: 10.9% vs. 8%; p=0.553) or presence of LVSI (11.5% vs. 9.4%; p=0.725) ( table 2 ). Conclusion: We have demonstrated that in patients with HPV-associated tumour types, negative regional lymph nodes, and tumour size ≤2 cm, oncological outcome after FST is excellent, and it is not inferior after non-radical cervical procedures.